Comparison of tumor-associated YAP1 fusions identifies a recurrent set of functions critical for oncogenesis - Szulzewsky, Frank; Kawauchi, Daisuke; Pajtler, Kristian Wilfried (Genes & development, 2020)
A biweekly scientific journal publishing high-quality research in molecular biology and genetics, cancer biology, biochemistry, and related fields